Application of Simple Additive Weighting Method for Decision Making for Scholarship Recipients at SMA Angkasa Adisutjipto Yogyakarta - Indrianingsih, Yuliani; Pujiastuti, Asih; Mauidzhoh, Uyuunul; Leo, Muhammad; Nuryatno, Edi Triono (Institut Teknologi Dirgantara Adisutjipto, 2024)
The SMA Angkasa Adisucipto Yogyakarta scholarship selection process requires an effective and objective approach to ensure that scholarships are awarded to students who meet the relevant criteria. The purpose of this study is to apply the Simple Weighting (SAW) method as a decision support in selecting scholarship recipients. The SAW technique was chosen because it allows for weighting calculations, allowing for a more systematic analysis of the criteria. The criteria used include student academic performance, attendance, behavior, and financial situation, each of which is weighted according to its importance. Eligible student data is processed using the SAW method to determine the final preference score, which is then used to rank prospective scholarship recipients. The results of the study indicate that the SAW method can make accurate and transparent decisions in selecting scholarship recipients. The application of the SAW method not only increases the efficiency of selection, but also reduces the subjectivity that occurs in the evaluation. In summary, the SAW method is very suitable as a decision-making tool based on various criteria, especially in selecting grant recipients.